Cloud resource allocation method based on time collaboration - Bo YIN; Yun-yong ZHANG; Zhi-jun WANG; Bing-yi FANG; Wei-bin FENG (Tongxin xuebao)
According to the application in the cloud computing environment load and load change is difficult to predict the amount of real time.A resource allocation method based on cooperative time was designed,the application of this method in the process of operation,according to the load and the task processing time,formulate the resource allocation scheme for multi virtual machine cooperation.The method uses time collaborative to effectively reuse resource,improves the utilization rate of data center resources,and further reduces the cost of operation and maintenance of data center.It has realistic significance to the increase of cloud resource provider profit.